Implementation of Web-Based Marketing System Technology for Bakat Jaya MSMEs, Magelang - Aji, Nurseno Bayu; Yudantoro, Tri Raharjo; Mardiyono, Mardiyono; Kurnianingsih, Kurnianingsih; Yanwari, Muhammad Irwan; Kuntarjo, Samuel Beta; Anif, Muhammad; Wiktasari, Wiktasari; Prayitno, Prayitno; Triyono, Liliek (Edumedia Solution, 2025)
This study explores a digital transformation initiative implemented for UMKM Bakat Jaya, a micro-enterprise based in Magelang specializing in animal feed production. Initially hindered by limited market reach, low digital literacy, and a lack of integrated technological tools, the enterprise relied primarily on traditional social media platforms for promotion. To address these challenges, a comprehensive and user-friendly website was developed using WordPress, featuring a professional company profile, product gallery, contact information, and seamless integration with existing social media accounts. The project was executed in four key phases: needs identification, website design and development, training and mentoring, and implementation followed by evaluation. Remote interviews and surveys were conducted to assess the partner’s needs, while capacity-building activities empowered stakeholders to manage the digital platform independently. Preliminary outcomes indicate a substantial improvement in market visibility, customer engagement, and operational efficiency. The results highlight the potential of structured digital interventions to transform the promotional strategies of rural micro and small enterprises, offering a scalable and sustainable model for enhancing competitiveness in similar contexts.